Recurrent Coxsackievirus Infection in a Patient with Lamellar Ichthyosis. Issue 2 (29th January 2016) - Damsky, William E.; Leventhal, Jonathan S.; Khalil, David; Vesely, Matthew D.; Craiglow, Brittany G.; Milstone, Leonard M.; Choate, Keith A.
Abstract: We describe a case of coxsackievirus (CV) A6 infection in a patient with lamellar ichthyosis followed by subsequent CV A8 infection within the same year. Atypical cutaneous features characterized the infection. This observation, combined with the rapidity with which reinfection occurred, suggests that the natural history of CV infection may be altered in patients with underlying ichthyoses.